Exploring Self-regulation of More or Less Expert College-Age Video Game Players: A Sequential Explanatory Design - Yilmaz Soylu, Meryem; Bruning, Roger H. (Frontiers in Psychology, 2016)
This study examined differences in self-regulation among college-age expert, moderately expert, and non-expert video game players in playing video games for fun. Winne’s model of self-regulation (Winne, 2001) guided the study. Main assumption of this study was that expert video game players used more processes of self-regulation than the less-expert players. We surveyed 143 college students about their game playing frequency, habits, and use of self-regulation. Data analysis indicated that while playing recreational video games, expert gamers self-regulated more than moderately expert and non-expert players and moderately expert players used more processes of self-regulation than non-experts. Semi-structured interviews also were conducted with selected participants at each of the expertise levels. Qualitative follow-up analyses revealed five themes: 1) characteristics of expert video gamers, 2) conditions for playing a video game, 3) figuring out a game, 4) how gamers act and, 5) game context. Overall, findings indicated that playing a video game is a highly self-regulated activity and that becoming an expert video game player mobilizes multiple sets of self-regulation related skills and processes. These findings are seen as promising for educators desiring to encourage student self-regulation, because they indicate the possibility of supporting students via recreational video games by recognizing that their play includes processes of self-regulation.